Una pieza más en la Justicia restaurativa empresarial: programas de cumplimiento restaurativos = Another piece in corporate Restorative Justice : restorative compliance programmes - Nieto Martín, Adán (Revista de victimología, 2023)
Compliance programmes, according to the most common definition, are a management tool for organisations that serve to prevent, detect and internally sanction behaviour that is contrary to the normative commitments that the organisation has assumed, whether they come from the legal system or are assumed voluntarily by the entity. Restorative justice, on the other hand, is a methodology for resolving conflicts caused by unlawful behaviour, with the aim of restoring the situation through a dialogue procedure, governed by a set of values (protagonism, recognition, restoration, accountability). However, compliance programmes are indispensable for resolving social conflicts arising from corporate violence, when there is damage resulting from unlawful behaviour. At the same time, it can also be seen how the design of compliance programmes according to restorative values allows them to be more efficient in their task: to get the members of the organisation to respect the rules.